What Do Elected Councillors Do in Long-Term Care Systems? Understanding the Contribution of Political Leaders - Catherine Needham; Catherine Mangan; Dave McKenna; Billie Cooper (Journal of Long-Term Care)
Context: This article fills a gap in the literature on long-term care by focusing on the role of local elected officials. The balance between local and national influence over long-term care varies by country. We here focus on England, where local elected councillors make key decisions on the design and delivery of support for frail older people and disabled people.